International mobility programs to improve soft skills of Vocational College students and alumni - Andri Handayani; Wahyu Kartika Wienanda (Intelektual Pustaka Media Utama, 2020)
In the workplace, hard skills and soft skills are equally taken into account, especially in this 21st century, where people are required to have ‘global employability skills’ to secure a good job. This study aims to determine the benefits of international mobility programs have on the ability of soft skills, especially in the aspects of communication, social skills and flexibility—as parts of ‘global employability skills’–of students and alumni of a Vocational College within three years from 2017 to 2019. The research method used is by distributing questionnaires Google Form with Likert Scale format from strongly disagree to strongly agree scale 1-5. Research subjects were active students and graduates of Vocational College (Sekolah Vokasi) UGM who had participated in international mobility programs, both incoming and outgoing programs, organized by the OIA SV-UGM, in 2017-2019. The respondents were 60 people. The results showed that the developed soft skills were language and communication skills, interpersonal skills, teamwork, cultural understanding and adaptability and openness. Specifically for alumni, soft skills that are highly developed and helpful in the working world are adaptability and openness (82.9%), cultural understanding (74.3%), language and communication skills (71.4%), ability to work together (65.7%), and interpersonal skills (54.3%).